Human IgG1 Responses to Surface Localised Schistosoma mansoni Ly6 Family Members Drop following Praziquantel Treatment. - Iain W Chalmers; Colin M Fitzsimmons; Martha Brown; Christine Pierrot; Frances M Jones; Jakub M Wawrzyniak; Narcis Fernandez-Fuentes; Edridah M Tukahebwa; David W Dunne; Jamal Khalife; Karl F Hoffmann (Public Library of Science (PLoS), 2015)
The heptalaminate-covered, syncytial tegument is an important anatomical adaptation that enables schistosome parasites to maintain long-term, intravascular residence in definitive hosts. Investigation of the proteins present in this surface layer and the immune responses elicited by them during infection is crucial to our understanding of host/parasite interactions. Recent studies have revealed a number of novel tegumental surface proteins including three (SmCD59a, SmCD59b and Sm29) containing uPAR/Ly6 domains (renamed SmLy6A SmLy6B and SmLy6D in this study). While vaccination with SmLy6A (SmCD59a) and SmLy6D (Sm29) induces protective immunity in experimental models, human immunoglobulin responses to representative SmLy6 family members have yet to be thoroughly explored.Using a PSI-BLAST-based search, we present a comprehensive reanalysis of the Schistosoma mansoni Ly6 family (SmLy6A-K). Our examination extends the number of members to eleven (including three novel proteins) and provides strong evidence that the previously identified vaccine candidate Sm29 (renamed SmLy6D) is a unique double uPAR/Ly6 domain-containing representative. Presence of canonical cysteine residues, signal peptides and GPI-anchor sites strongly suggest that all SmLy6 proteins are cell surface-bound. To provide evidence that SmLy6 members are immunogenic in human populations, we report IgG1 (as well as IgG4 and IgE) responses against two surface-bound representatives (SmLy6A and SmLy6B) within a cohort of S. mansoni-infected Ugandan males before and after praziquantel treatment. While pre-treatment IgG1 prevalence for SmLy6A and SmLy6B differs amongst the studied population (7.4% and 25.3% of the cohort, respectively), these values are both higher than IgG1 prevalence (2.7%) for a sub-surface tegumental antigen, SmTAL1. Further, post-treatment IgG1 levels against surface-associated SmLy6A and SmLy6B significantly drop (p = 0.020 and p < 0.001, respectively) when compared to rising IgG1 levels against sub-surface SmTAL1.Collectively, these results expand the number of SmLy6 proteins found within S. mansoni and specifically demonstrate that surface-associated SmLy6A and SmLy6B elicit immunological responses during infection in endemic communities.